Incidence and prognostic significance of nephrotoxicity in patients receiving eshap as salvage therapy for lymphoma. (July 2017) - Sorigue, Marc; Sancho, Juan-Manuel; Pineda, Alberto; Garcia, Olga; Lopez, David; Moreno, Miriam; Tapia, Gustavo; Batlle, Montse; Ferra, Christelle; Vives, Susanna; Ibarra, Gladys; Feliu, Evarist; et al.
Highlights: We examined the incidence and impact of ESHAP nephrotoxicity in lymphoma patients. Nephrotoxicity was more common in outpatients than inpatients (14/39 vs. 4/35). Patients with renal failure at the time of ASCT had an inferior overall survival. Outpatient administration of ESHAP may not be optimal for all patients. Abstract: Nephrotoxicity is a well-known side effect of platinum-based chemotherapy. We retrospectively assessed the incidence and prognostic impact of nephrotoxicity with ESHAP rescue chemotherapy in 74 lymphoma patients (61 aggressive lymphomas). A higher incidence of nephrotoxicity (estimated glomerular filtration rate <60 mL/min) was found when ESHAP was administred on an outpatient vs. inpatient basis (14/39 vs. 4/35). Patients submitted to ASCT with renal failure had a lower overall survival (OS) than those with normal renal function (2-yr OS probability [95%CI]: 88% [77%–99%] vs. 50% [22%–78%]). Outpatient administration of ESHAP may not be optimal for all patients and the impact of ESHAP-induced renal failure on ASCT outcomes in lymphoma needs to be assessed in prospective studies.